Review of Russian Abstracts Accepted for United European Gastroenterology Week (2022) - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present an analysis of the Russian abstracts published in the materials of the 30th. United European Gastroenterology Week (UEGW).Key points. In the materials of 30 UEGW, 17 abstracts of Russian authors from Moscow, St. Petersburg, Novosibirsk, Kazan and other cities were published. The abstracts were devoted to topical issues of pathogenesis, diagnosis and treatment of intestinal liver and pancreatic diseases.Conclusion. Analysis of the published abstracts testifies to the high scientific level and large practical significance of the conducted research.